Comparative study on transition metal promoted Pt/SiO2 for oxidative dehydrogenation of propane with carbon dioxide - Heng-Bo Zhang; Guo-Qing Yang; Jiageng Li; Zhong-Wen Liu (Journal of CO2 Utilization)
Transition metal is quantitatively investigated as a promoter of Pt-supported catalysts for the oxidative dehydrogenation of propane with CO2 (CO2-ODP). However, the criteria for selecting the transition metal are largely from trial and error. In this work, Pt/SiO2 catalysts promoted with 3d transition metals (TMs) of Mn, Fe, Co or Ni (PtTM/SiO2) are comparatively studied for CO2-ODP. We found that the C3H6 selectivity and conversions of propane and CO2 are clearly improved when TMs are introduced into Pt/SiO2. Moreover, the apparent activation energy for the C3H6 formation during CO2-ODP is decreased in the order of PtNi/SiO2 > PtCo/SiO2 > PtFe/SiO2 > PtMn/SiO2. Among the investigated catalysts, PtMn/SiO2 is the most active and selective catalyst for the activation of C-H bonds in propane to produce C3H6 while PtNi/SiO2 is the most favorable catalyst for the formation of by-products via the dry reforming of propane with CO2 and propane cracking. Essentially, the catalytic results are well explained as the increased electron density of Pt over the PtTM/SiO2 catalysts via the enhanced electron transfer from TM having a smaller electronegativity. This understanding is important for the rational design of a high-performance Pt-based bimetallic catalyst for CO2-ODP.